"The dark side of the spectrum …" a "day of suffering" for medical students. Issue 1 (1st June 2003) - Lewis, W; Grant, A
Abstract : The alleviation of suffering has been described as a central goal of medicine. A familiarity with this subject may have great practical benefit, while promoting reflection upon medicine more generally. This paper describes a study day for medical students that encourages them to think about suffering. A variety of texts in different media were used as the basis of group discussion. Sources reflected the range of suffering that may be encountered, including suffering from causes not normally considered to be "medical". An evaluation of the study day was performed, using the nominal group technique, suggesting that the day was both popular and had achieved its goals.